2021
DOI: 10.1111/jocs.15305
|View full text |Cite
|
Sign up to set email alerts
|

Status of coronary disease and results from early endovascular aneurysm repair after preventive percutaneous coronary revascularization

Abstract: Background The incidence of coronary artery disease (CAD) is high in patients with an aortic aneurysm but preoperative routine coronary angiography and preventive coronary revascularization are not recommended to reduce cardiac events in patients with severe CAD. Aim This study evaluated the safeness and efficacy of preventive percutaneous coronary intervention (PCI) in patients with severe CAD scheduled for endovascular aneurysm repair (EVAR). Methods All patients with descending thoracic aneurysm (DTA) or ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Whether PCI can reduce mortality or MI in patients with stable CAD remains controversial ( 21 ). In patients with AA, however, several reports have suggested that appropriate management including coronary revascularization may improve clinical outcomes ( 4 , 22 ). Functional tests such as stress echocardiography or single-photon emission computed tomography could be alternatives to CACT for the detection of coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Whether PCI can reduce mortality or MI in patients with stable CAD remains controversial ( 21 ). In patients with AA, however, several reports have suggested that appropriate management including coronary revascularization may improve clinical outcomes ( 4 , 22 ). Functional tests such as stress echocardiography or single-photon emission computed tomography could be alternatives to CACT for the detection of coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%